CHALCIDOIDEA SPECIES (INSECTA: HYMENOPTERA) ON THE WOODY VINE CAMPSIS RADICANS (L.) SEEM. EX BUREAU (Acta Entomologica Serbica, 2018)
The woody vine Campsis radicans has extrafloral nectaries on the sepal, pedicel and green fruits. Its nectar attracts abundant Hymenoptera and especially representatives of the Chalcidoidea superfamily. During a six-year study (2012-2017) in the period from July to mid-October, 2117, specimens of Chalcidoidea from 13 families were collected. A total of 116 species were determined, of which 63 were new species to the Serbian fauna, and 11 to the fauna of the Balkan Peninsula. Campsis radicans can be considered as a “bait plant” that attracts many groups of Hymenoptera, which is very important for the study of their fauna, and in particular, for almost all the families of the Chalcidoidea superfamily. Campsis radicans is also significant since its extrafloral nectar is food to many Chalcidoidea species in periods when no other food is available. Given that almost all of the identified Chalcidoidea species are natural enemies of other insects (most commonly of phytophagous insects), C. radicans indirectly provides a natural balance in different terrestrial ecosystems.